What makes each of us unique? The nine-banded armadillo as a model to study individuality - Leao, Delva P.; Duque, Alvaro; Dietrich, Marcelo O. (Frontiers in Mammal Science, 2024)
The human brain is the foundation of our identity as a species and as individuals. It is where our unique sensations, emotions, and thoughts arise. The same way no two individuals are alike, no two brains are identical. Understanding the expression of inter-individual differences in brain and behavior and their underlying biological mechanisms can profoundly influence neuroscience and the science of individuality. Here, we argue that the nine-banded armadillo is a unique organism for the study of how inter-individual differences are expressed in the mammalian brain. Our argument is based on the fascinating reproductive biology of armadillos, the only known mammals that always generate offspring that are genetic clones, and on how this characteristic can help understand the complex interplay between genetic, environmental, and stochastic factors in the biology of individuality. We will first review the sources of variance in brain-related traits and behavior, then the biology of armadillos, and finally how they can aid in understanding the origins of variance in brain structure and function. Finally, we will provide an overview of the type of studies that can be performed using armadillos and how these studies can advance the science of individuality.